2022
DOI: 10.3389/fmicb.2022.924709
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial susceptibility profiles and tentative epidemiological cutoff values of Legionella pneumophila from environmental water and soil sources in China

Abstract: Legionnaires’ disease (LD), caused by Legionella, including the most prevalent Legionella pneumophila, has been treated primarily with antibiotics. Environmental water and soil are the reservoirs for L. pneumophila. Studying antimicrobial susceptibility using a large number of isolates from various environmental sources and regions could provide an unbiased result. In the present study, antimicrobial susceptibility of 1464 environmental L. pneumophila isolates that were derived from various environmental water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(116 reference statements)
1
2
0
Order By: Relevance
“…Previous studies have also reported the presence of the efflux pump gene in isolates whose MIC values for AZT are equal to or exceed 0.125 mg/L (Vandewalle-Capo et al, 2017;Nata and Løva, 2019;Portal et al, 2021b). However, the presence of lpeABnegative isolates with elevated MIC values as high as 0.5 mg/L was also observed in this study, and in previous works (Cocuzza et al, 2021;Yang et al, 2022). In this situation defining an ECOFF is a complex question given that the purpose is to discriminate between wild-type isolates and isolates containing acquired resistance mechanisms, and the efflux pump LpeAB has been described as an acquired resistance mechanism (Turnidge et al, 2006).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have also reported the presence of the efflux pump gene in isolates whose MIC values for AZT are equal to or exceed 0.125 mg/L (Vandewalle-Capo et al, 2017;Nata and Løva, 2019;Portal et al, 2021b). However, the presence of lpeABnegative isolates with elevated MIC values as high as 0.5 mg/L was also observed in this study, and in previous works (Cocuzza et al, 2021;Yang et al, 2022). In this situation defining an ECOFF is a complex question given that the purpose is to discriminate between wild-type isolates and isolates containing acquired resistance mechanisms, and the efflux pump LpeAB has been described as an acquired resistance mechanism (Turnidge et al, 2006).…”
Section: Discussionsupporting
confidence: 74%
“…Legionella is susceptible to erythromycin, clarithromycin, azithromycin, levofloxacin (LEV), and moxifloxacin (MOX) in clinical practice ( 29 ). Many antibiotic-resistant clinical isolates of L. pneumophila have been identified ( 30 ). These isolates were mainly azithromycin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with extrapulmonary involvement are often treated with fluoroquinolones ( 18 ). These three fluoroquinolones have similar minimum inhibitory concentrations against L. pneumophila ( 30 ). However, LEV requires dose adjustment according to renal function.…”
Section: Discussionmentioning
confidence: 99%